Strategi Peningkatan Kinerja Pegawai Diskominfo melalui Pemberlakuan Laporan Tahunan - Khairunnisak Nasution; Annio Indah Lestari Nasution (Journal Economic Excellence Ibnu Sina, 2024)
Increasing employee performance will bring progress for the company or organization to be able to survive in an unstable competitive work environment. The aim and benefit of the research as a result of the internship carried out by the author is so that the North Sumatra Province Communication and Information Service Office can optimize the performance of office employees through strategies that can create comfort and optimal performance for employees. The achievement of the service performance of the Medan City Communication and Informatics Service, in terms of ratio, can be said to be close to 90%, which includes all programs and activities as performance indicators in accordance with the main tasks and functions (TUPOKSI) of the Medan City Communication and Informatics Service, as well as the Minimum Service Standard targets ( SPM) outlined in the RENSTRA target of the Medan City Communication and Information Service for 2016-2021